Pengaruh Media Sosial Terhadap Perubahan Bahasa Gaul di Kalangan Remaja - Jasmine Azizah Nur Inayah; Ahmad Fadhel Arifin; Muhammad Rikki Akbar; Zulfania Andriani Safitri; Alika Rafeyfa Erina; Dewi Puspa Arum (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
This research aims to determine the influence of social media on language change slang among teenagers. Slang can be interpreted as puns and language styles used by teenagers to express themselves, and is often used in communication between peers. Slang itself has experienced development and modification from generation to generation. Nowadays, with the increasing popularity of social media, these platforms are becoming a forum for teenagers to share information, interact and develop new ideas. The method used in this research is a qualitative method through literature study from various social media, for example TikTok, Instagram, Facebook and X. Research results shows that social media plays a very important role in spreading new terms and slang among teenagers. Many slang words and creative terms emerged as a result the influence of trends and culture circulating on social media, which creates ways of communication which is more relaxed and flexible. Using slang on social media also helps teenagers form their identity, while creating differences in the way they communicate between the older and younger generations. Apart from that, this research also found that social media allows teenagers to adapt quickly to change Language.